Exercises with A Target Heart Rate both Safety and Effectiveness for Reducing Sedentary Effects During Pandemic of Covid-19 - Anak Agung Gede Eka Septian Utama; M. Widnyana; I Putu Yudi Pramana (Physical Therapy Journal of Indonesia, 2021)
Introduction: Limited activities will increase the risk of sedentary activity, so that it will become a new problem. Exercise is an effort to reduce sedentary activity and reduce boredom, maintain health, and increase the immune system. The right kind of exercise will have a good and bad impact. Therefore, this study aims to look at exercise with a target heart rate, safety and effectiveness, and reduce sedentary effects during the Covid-19 pandemic. Methods: The data used has been through literature studies obtained from research articles including PubMed, ScienceDirect, and Google Scholar. With keywords, including COVID-19 pandemic, sedentary effects, exercise, target heart rate. The data analysis technique used is argumentative, descriptive analysis. Results: Based on the literature view, the writer found ten related articles. This study provides evidence of the effect of exercise with target heart rate both safety and effectiveness for reducing sedentary effect. This article explained that it knows the exercise heart rate that the heart wants to reach and can be accepted by the heart, reduces lipid, increases the immune response, improves fitness and heart health. Conclusion: Exercises can use the target heart rate to provide an overview of the range of training zones you want to achieve and provide safety and effectiveness in exercising, especially the cardiovascular system.